Salpingectomy and prevention of ovarian carcinoma - Shahul Hameed Mohamed Siraj; Bernard Su Min Chern (Wolters Kluwer Medknow Publications, 2016)
Advanced cases of epithelial, primary peritoneal, and primary tubal malignancies have relative poor prognosis and collectively remain the most deadly of all gynecologic malignancies. Recently, many studies have demonstrated that the fallopian tubes might be the origin of most high grade ovarian and peritoneal serous carcinoma. In this review, we describe the tubal carcinogenic pathway with the precancerous tubal lesions and the impact of salpingectomy for prevention of ovarian carcinoma.